Push and Pull Factors Driving Victims of Human Trafficking Toward Middle East Countries: The Case of Victims Moving out of Ethiopia via the Eastern Route - Dita Tuse; Tesfaye Boyosa; Wondu Teshome, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The continuation and escalation of human trafficking has become a challenging problem for the world community who tries to stem its flow. People move from one part to another part of the world either lured by the booming economy elsewhere or to escape the deterioration of life in their home country. This study is conducted to highlight factors   driving victims of human trafficking from Ethiopia via the eastern route of the country to cross the borders. The study focuses on the situation of returnee victims of human trafficking and partially household heads. Snow ball sampling techniques was employed and 36 returnee victims participated. In addition 10 household heads of victims were interviewed. The researchers employed simple statistics (frequency and percentage), interpretation, and conceptual generalization to analyze data. The results showed that unemployment, pressure from family and friends; false promises of better job opportunity, contributed at varying degrees.  On the basis of these findings, we recommend the launching of an awareness raising campaign on trafficking dangers with the participation of experienced former victims of trafficking together with organizing entrepreneurship skills training for local people based on existing opportunities and resources in their areas.Received 25th December 2017; Revised 18th July 2018; Accepted 10th October 2018